Perpajakan Indonesia di Era Teknologi dan Keterbukaan Informasi Keuangan - Yessica Amelia; Muhammad Rizal; Ranti Karlaili (Jurnal Pengabdian Masyarakat Nusantara, 2021)
Digital economic transactions have emerged as a result of Indonesia's technological and financial information advancements. In order to optimize tax revenue, the Indonesian government adapt and respond to the growing prevalence of digital transactions, especially e-commerce. The primary obstacles include finding a clear definition for digital economic enterprises, enacting legislation governing digital transactions that are compliant with international standards, and allocating resources in a way that optimizes the advantages of digital economic transactions. By creating electronic platforms like DJP-online, the Indonesian government hopes to improve the ease and openness of the tax filing procedure. In an effort to maximize tax revenue in the digital age, tax advisors play a crucial role, and society must change to embrace technology. To ensure a smooth and successful rollout of the digital tax system, the Indonesian government must constantly update rules, enhance public education efforts, and improve online services. This community engagement activity discussed the material through online webinars, providing an accessible platform for all participants to gain insights into the digital taxation landscape and aiding the government in socializing regulations in the field of digital taxation